Disinfection Byproducts in Drinking Water and Evaluation of Potential Health Risks of Long-Term Exposure in Nigeria - Benson, Nsikak U. (J Environ Public Health, 2017)
Levels of trihalomethanes (THMs) in drinking water from water treatment plants (WTPs) in Nigeria were studied using a gas chromatograph (GC Agilent 7890A with autosampler Agilent 7683B) equipped with electron capture detector (ECD). The mean concentrations of the trihalomethanes ranged from zero in raw water samples to 950 μg/L in treated water samples. Average concentration values of THMs in primary and secondary disinfection samples exceeded the standard maximum contaminant levels. Results for the average THMs concentrations followed the order TCM > BDCM > DBCM > TBM. EPA-developed models were adopted for the estimation of chronic daily intakes (CDI) and excess cancer incidence through ingestion pathway. Higher average intake was observed in adults (4.52 × 10(−2) mg/kg-day), while the ingestion in children (3.99 × 10(−2) mg/kg-day) showed comparable values. The total lifetime cancer incidence rate was relatively higher in adults than children with median values 244 and 199 times the negligible risk level.